Front Cover: Stereospecific Access to α‐ and β‐N‐Glycosylamine Derivatives by a Metal Free O‐to‐N [3, 3]‐Sigmatropic Rearrangement (Eur. J. Org. Chem. 41/2022). Issue 41 (25th October 2022) - Pratesi, Debora; Mirabella, Stefania; Petrucci, Giulia; Matassini, Camilla; Faggi, Cristina; Cardona, Francesca; Goti, Andrea
Abstract : The Front Cover exhibits a photo of the famous Ponte Vecchio (Old Bridge) on the Arno River, as a tribute to the city of Florence and its University, where all the research has been carried out. Allegorically, the Old Bridge reflecting on the water surface represents the two faces of the sugar derivative on which the rearrangement may take place: from top (the Old Bridge) or bottom (the mirrored Old Bridge). Cover picture created by the skill of Dr. Marco Bonanni. More information can be found in the Research Article by A. Goti et al .